ANTIBIOTIC RESISTANCE AND SUSCEPTIBILITY PATTERNS OF STAPHYLOCOCCUS AUREUS ISOLATES IN RAW CHICKEN GIZZARDS FROM SELECTED RETAILERS IN KATABI SUB-COUNTY, WAKISO DISTRICT, UGANDA. A CROSS-SECTIONAL STUDY. - Nakkungu, Jackline (Student’s Journal of Health Research Africa, 2023)
Introduction: Compromised public health structures, poor disease surveillance, antimicrobial resistance, enterotoxin production, poor educational program approaches, and local law enforcement in addition to other factors have led to food-borne illness as a great public health concern and these are commonly under-reported. This study examines raw chicken gizzards. Methodology: Across sectional study was done on the fresh raw chicken gizzards randomly selected from different supermarkets and fresh poultry product outlets which were then transported at 4˚C to the microbiology laboratory for culture and antibiotic susceptibility testing. Results: A total of 39 raw chicken gizzards randomly selected from different fresh chicken outlets were used in the study to test for the presence of Staphylococcus aureus. Findings showed that 10 samples were positive for Staphylococcus aureus. The results show that out of the 10 samples found positive in the Coagulase slide test for staphylococcus aureus, 6/10 (60%) were resistant to Penicillin (P), 9/10 (90%) were resistant to vancomycin(Va), 9/10 (90%) were resistant to Ampicillin(Amp),4/10 (40%) were resistant to Cefoxitin(FOX) and 10/10 (100%) were resistant to Tetracycline(TE). Conclusion and recommendation: This study demonstrated that the Staphylococcus species have entered the food chain. Recommendation As the amounts were low, the pathogen is not likely to cause disease, especially if chicken gizzards are properly prepared before consumption.